EFFICACY OF THE TRIS AND BIOCIPHOS PLUS EXTENDERS ON THE FREEZABILITY OF PUNGANUR BULL SEMEN - VEERABRAMHAIAH, K; RAO, A SESHAGIRI; RAO, V H; NAIDU, K VENUGOPAL; RAO, S T VIROJI (The Indian Journal of Animal Reproduction, 2023)
The present investigation was carried out to study the freezability of Punganur bull semen with Tris andBiociphos plus extenders. The difference in the individual sperm motility and live sperms between fresh andBiociphos plus extended semen and between Tris and Biociphos plus extended semen during pre-freeze andpost-thaw periods was significant. The difference in head, mid- piece, tail and total sperm abnormalities betweenfresh and Tris extended semen was not significantly different but between Tris and Biociphos plus extendedsemen during pre-freeze and post-thaw periods was significant. Both the extenders were relatively non-toxic tosperm, but based on the sperm motility, livability, sperm abnormalities and acrosome damage Tris extender wasconcluded a better choice for preservation of Punganur bull semen.
Keywords: Punganur bulls; Semen; Freezability; Tris buffer; Biociphos Plus